Coated battery separator, preparation method and secondary battery

By applying a ceramic coating with adhesive microspheres embedded on the battery separator, the problem of Hi-Pot defect caused by large-grain glue falling off is solved, the adhesion and thermal stability of the separator are improved, and the effects of high adhesion and low Hi-Pot defect rate are achieved.

CN119786883APending Publication Date: 2025-04-08SINOMA LITHIUM BATTERY SEPARATOR CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411996672.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing mixed-coated separators embedded with large-grain glue are prone to poor Hi-Pot due to the fall of large-grain glue, and the heat shrinkage and powder dropping rate are insufficient, which affects the safety and performance of the battery.

Method used

A ceramic coating containing inorganic particles is used to coated battery separators with adhesive microspheres embedded in them. By controlling the embedded depth and convexity of the adhesive microspheres, the adhesion and ion transport capacity of the separator are improved, and the heat shrinkage and powder drop rate are improved.

Benefits of technology

It achieves high adhesion and low Hi-Pot defect rate, improves the thermal stability and powder drop rate of the diaphragm, and ensures the safety and performance of the battery at high temperatures and during use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786883A_ABST
    Figure CN119786883A_ABST
Patent Text Reader

Abstract

The present invention provides a coated battery separator, comprising a base film and a ceramic coating embedded with sticky microspheres coated on the surface of the base film; the embedding depth h of any sticky microsphere and the thickness H of the ceramic coating satisfy H / 3≤h≤H / 2. The structure designed by the present invention to reduce the embedding depth of large particle glue (polymer microsphere) in the ceramic coating and its regulation method can have a low powder loss rate under the premise of high adhesion and ion transport capacity. Even if some local large particle glue falls off due to friction, the coated separator still has sufficient electrical strength to isolate the positive and negative electrodes during the battery cell assembly process, reducing the Hi-Pot defect rate after hot pressing during the battery assembly process, and achieving a better balance between the high adhesion of the separator and the low Hi-Pot defect rate of the battery cell after hot pressing. The present invention also provides a preparation method of the coated battery separator with high adhesion and low Hi-Pot defect and a secondary battery containing the coated battery separator.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium-ion battery separators, and in particular relates to a coated battery separator and a preparation method thereof, as well as a secondary battery using the coated battery separator. Background Art

[0002] As one of the key components of lithium-ion batteries, the diaphragm is located between the positive and negative electrodes of the battery. It has the function of isolating the positive and negative electrodes and conducting lithium ions. The selection of diaphragm material is crucial to the safety of the battery. Polyolefin materials are currently widely used in the manufacture of battery diaphragms because of their excellent chemical stability, good insulation properties, appropriate pore size and porosity, and certain mechanical strength and flexibility. Existing diaphragms generally use high-strength thin-film polyolefin porous membranes.

[0003] Traditional polyolefin separators have the defects of low melting point and insufficient thermal stability. When the battery is abnormally heated, the polyolefin separator is prone to shrinkage, resulting in the inability to effectively isolate the positive and negative electrodes, causing the risk of internal short circuit in the battery. The current conventional solution is to coat inorganic ceramic materials on the base film to improve the thermal shrinkage level of the separator, so that it can withstand high temperatures of 130°C, and the 1h thermal shrinkage size is maintained at the level of MD<3.0 and TD<2.5. In addition, in order to cope with the problem of wrinkling between the battery pole piece and the separator during the assembly of the battery under the current background of accelerated battery assembly, resulting in poor appearance of the battery cell, an embedded mixed-coating separator has gradually been developed, and large-particle glue of polymer material has been introduced to increase the adhesion between the pole piece and the separator, but this also creates the problem of increased defective rate of lithium battery products in Hi-Pot (High Potential Test, dielectric withstand voltage test). Hi-Pot of lithium battery is to apply voltage between mutually insulated parts or between an independent part and the ground for a period of time to test the insulation tolerance of the material under rated voltage or instantaneous overvoltage caused by switching, arcing and other similar phenomena. With the introduction of large-particle glue, especially for single-sided mixed-coating products, during the use of the battery, the base film is exposed due to the shedding of large particles, which becomes a weak breakdown point during the Hi-Pot (High Potential Test) of the battery cell.

[0004] In view of the above-mentioned technical problems existing in the current battery separators, it is urgent to develop a new type of coated battery separator that can maintain high adhesion while maintaining a low Hi-Pot defective rate of the assembled battery cells. Summary of the invention

[0005] The present invention aims to solve the problem that the mixed-coated diaphragm embedded with large-particle glue in the prior art is prone to Hi-Pot failure due to the shedding of large-particle glue. It can effectively improve the adhesion and ion transport capacity, and further improve the thermal shrinkage and powder loss rate of the diaphragm, provide a coated battery diaphragm with high adhesion and low Hi-Pot failure, a preparation method and a secondary battery, and achieve a better balance between the high adhesion of the diaphragm and the low Hi-Pot failure rate of the battery cell after hot pressing.

[0006] In order to solve the above technical problems, the present invention provides a coated battery separator, comprising a base film and a coating coated on at least one surface of the base film, wherein the coating is a ceramic coating containing inorganic particles, and a plurality of sticky microspheres are embedded in the ceramic coating; the contact surface between the ceramic coating and the base film is the inner surface, and the other opposite surface is the outer surface, the vertical distance between the bottom of the sticky microsphere and the outer surface is the embedding depth h, the thickness of the ceramic coating is H, and for any of the sticky microspheres, H / 3≤h≤H / 2 is satisfied.

[0007] Preferably, 60 to 98% of the number of said adhesive microspheres protrude from said outer surface of said ceramic coating, preferably 75 to 98%.

[0008] Preferably, the material of the inorganic particles includes one or more of α-alumina, γ-alumina, boehmite, calcium carbonate, barium sulfate, barium titanate, hydrotalcite, montmorillonite, spinel, titanium dioxide, silicon dioxide, zirconium dioxide, magnesium oxide, calcium oxide, beryllium oxide, magnesium hydroxide, calcium hydroxide and silicon carbide.

[0009] Preferably, the median particle size D of the inorganic particles is v50 The thickness is preferably 0.05 to 1.5 μm, more preferably 0.1 to 1.0 μm.

[0010] Preferably, the sticky microspheres are polymer microspheres, and their materials include one or more of polyimide, styrene-butadiene rubber, modified polyacrylate, polyetherimide, aramid, aramid fiber, polyvinylidene fluoride, polymethyl methacrylate or its grafted copolymer, thermoplastic polyurethane elastomer rubber, polyethylene terephthalate, polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride and polyvinylidene fluoride-hexafluoropropylene; further preferably, the sticky microspheres are made of polymethyl methacrylate (PMMA, Poly(methyl methacrylate)) or styrene-grafted polymethyl methacrylate.

[0011] As the material of the viscous microspheres, PMMA or styrene-grafted PMMA is preferred, the glass transition temperature of the material is 30 to 110°C, more preferably 45 to 75°C, and even more preferably 50 to 55°C; the median particle size D of the viscous microspheres is v50The diameter of the adhesive microspheres is 1 to 10 μm, preferably 3 to 6 μm, and the density of the adhesive microspheres is 1.1 to 1.3 g / cm 3 , preferably 1.11 to 1.2 g / cm 3 .

[0012] As a preferred embodiment of the above-mentioned sticky microspheres, the solid matter mass ratio of the inorganic particles to the sticky microspheres is 11:1 to 30:1, preferably 13:1 to 25:1.

[0013] Preferably, the base film is made of polyethylene and / or polypropylene, and has a thickness of 5 to 15 μm.

[0014] As a preferred embodiment of the above technical solution, one or both surfaces of the base film are coated with the ceramic coating.

[0015] The present invention also provides a method for preparing the aforementioned high-adhesion and low-Hi-Pot coated battery separator, comprising at least the following steps:

[0016] (1) preparing a slurry: mixing and dispersing inorganic particles with a dispersion medium to form an inorganic dispersion, then adding a solution of viscous microspheres, dispersing the particles uniformly and sieving the mixture to obtain a mixed slurry, wherein the prepared slurry includes at least the mixed slurry;

[0017] (2) coating: coating the slurry onto a base film to form a ceramic coating layer embedded with adhesive microspheres on the base film;

[0018] (3) Drying: Drying the base film coated with the slurry to obtain the coated battery separator with high adhesion and low Hi-Pot defect.

[0019] The solid content of the slurry is 28-40%. The material of the sticky microsphere is PMMA or its graft copolymer, the solid content of PMMA or its graft copolymer in the sticky microsphere solution is 15-30%, and the density of the sticky microsphere raw material is 1.1-1.3 g / cm 3 , preferably 1.11 to 1.2 g / cm 3 .

[0020] Preferably, in the step (1), the slurry also includes a ceramic slurry without adhesive microspheres, and the inorganic particles are mixed with a dispersion medium, dispersed evenly and sieved to obtain the ceramic slurry; in the step (2), the ceramic slurry is first coated on the base film, and then the mixed slurry is coated after drying.

[0021] Preferably, in the step (2), a coating machine is used to coat the mixed slurry onto the base film, and the coating speed is 50 to 250 m / min, more preferably 100 to 150 m / min.

[0022] As a preferred mixed coating slurry, the mixed coating slurry also contains one or any multiple of a thickener, a binder, a wetting agent and a dispersant; further preferably, the mass percentage of each component is: inorganic particles 25-46%, sticky microspheres 1-30%, binder 2-10%, thickener 0.1-5%, dispersant 0.01-3%, wetting agent 0.01-3% and dispersion medium 50-80%.

[0023] As a preferred ceramic slurry, the mixed slurry also contains one or any multiple of a thickener, a binder, a wetting agent and a dispersant; further preferably, the mass percentage of each component is: inorganic particles 25-46%, binder 1-10%, thickener 0.1-5%, dispersant 0.01-3%, wetting agent 0.01-3% and dispersion medium 40-60%.

[0024] As the binder, preferably, the binder is one or any combination of styrene-butadiene rubber, acrylate, polyvinyl alcohol, polyacrylonitrile, polyvinylidene fluoride, polyethylene oxide and polytetrafluoroethylene; more preferably, the binder is acrylate.

[0025] As the preferred thickener, the thickener is one or more of sodium carboxymethyl cellulose, carboxymethyl cellulose, lithium carboxymethyl cellulose, sodium alginate, polyacrylamide, polyacrylic acid, polyvinyl alcohol, polyimide and cellulose; more preferably, polyether-modified siloxane.

[0026] As the preferred wetting agent, the wetting agent is one or more of anionic surfactants, polyethylene surfactants and polyol surfactants, and more preferably polyether-modified siloxane.

[0027] As a preferred dispersant, the dispersant is one or any combination of polyvinyl pyrrolidone, polyacrylamide and polyvinyl alcohol.

[0028] As a preferred embodiment of the above technical solution, in the step (2), the mixed coating slurry is coated on one or both surfaces of the base film to form a base film with a ceramic coating on one or both sides.

[0029] The present invention also provides a secondary battery, comprising the aforementioned coated battery separator, or comprising a coated battery separator prepared by the aforementioned method for preparing the coated battery separator.

[0030] The above technical scheme of the present invention designs a structure for reducing the embedding depth of large particle glue (polymer microspheres) in the ceramic coating and its regulation method, and its beneficial effects are: it can have a low powder loss rate under the premise of having high adhesion and ion transport capacity, and even if some local large particle glue falls off due to friction, the coated diaphragm still has sufficient electrical strength to isolate the positive and negative electrodes during the battery cell assembly process, reducing the Hi-Pot defective rate after hot pressing during the battery assembly process, and achieving a better balance between the high adhesion of the diaphragm and the low Hi-Pot defective rate of the battery cell after hot pressing. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The following drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the specific implementation, they are used to explain the present invention but do not constitute a limitation of the present invention. They include:

[0032] Figure 1 This is a scanning electron microscope image of the cross section of the coated battery separator provided by the present invention (accelerating voltage 1.0 kV, working distance 4.2 mm, SE2 detector, magnification 200);

[0033] Figure 2 A scanning electron microscope image (accelerating voltage 1.0 kV, working distance 4.2 mm, SE2 detector, magnification 200) of a cross section of a coated battery separator is provided for the present invention;

[0034] Figure 3 A schematic diagram of a drying step in the method for preparing a coated battery separator provided by the present invention;

[0035] Figure 4 Schematic diagram of the structure of the viscous microspheres embedded in the ceramic coating in the coated battery separator provided by the present invention:

[0036] Wherein, R is the radius of the sticky microsphere, Δh is the height of the sticky microsphere protruding from the upper surface of the ceramic coating, h is the embedding depth of the sticky microsphere into the ceramic coating, and H is the thickness of the ceramic coating. DETAILED DESCRIPTION

[0037] In order to make the technical problems, technical solutions and advantages to be solved by the present invention clearer, the following will be described in detail with reference to the accompanying drawings and specific test examples. It should be understood that the specific implementation methods described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0038] For existing problems, such as Figure 1 to Figure 2As shown, the first aspect of the present invention provides a coated battery separator, comprising a base film and a coating coated on at least one surface of the base film, wherein the coating is a ceramic coating containing inorganic particles, and a plurality of sticky microspheres are embedded in the ceramic coating: the contact surface between the ceramic coating and the base film is the inner surface, the other opposite surface is the outer surface, the vertical distance between the bottom of the sticky microsphere and the outer surface is the embedding depth h, the thickness of the ceramic coating is H, and for any sticky microsphere, H / 3 is satisfied <h<H / 2。

[0039] In the present invention, if the embedding depth h of the sticky microspheres is too large, the adhesion of the diaphragm surface to the pole piece is weakened, affecting the bonding force of the battery diaphragm to the pole piece. If the embedding depth h of the sticky microspheres is too small, the affinity of the diaphragm to the pole piece becomes poor, and the powder loss rate of the diaphragm is affected, thereby affecting the high-temperature stability of the diaphragm.

[0040] As a preferred embodiment of the present invention, 60 to 98% of the sticky microspheres protrude from the outer surface of the ceramic coating, for example, it can be 60%, 65%, 70%, 72%, 75%, 78%, 80%, 82%, 85%, 88%, 89%, 90%, 91%, 92%, 94%, 96% and 98%; preferably 75 to 98%.

[0041] In the present invention, the proportion of the sticky microspheres protruding from the outer surface of the ceramic coating is controlled within the range, which helps to achieve a balance between the adhesion of the diaphragm and the high-temperature stability of the diaphragm, and on this basis, effectively improves the powder loss rate of the diaphragm.

[0042] As a preferred embodiment of the present invention, the material of the inorganic particles includes one or more of α-alumina, γ-alumina, boehmite, calcium carbonate, barium sulfate, barium titanate, hydrotalcite, montmorillonite, spinel, titanium dioxide, silicon dioxide, zirconium dioxide, magnesium oxide, calcium oxide, beryllium oxide, magnesium hydroxide, calcium hydroxide and silicon carbide.

[0043] As a preferred embodiment of the present invention, the median particle size D of the inorganic particles is v50 It is 0.05 to 1.5 μm, such as 0.05 μm, 0.1 μm, 0.2 μm, 0.25 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 1 μm, 1.2 μm, 1.4 μm and 1.5 μm, and 0.1 to 1.0 μm is more preferred.

[0044] As a preferred embodiment of the present invention, the viscous microspheres are polymer microspheres, and their materials include one or more of polyimide, styrene-butadiene rubber, modified polyacrylate, polyetherimide, aramid, aromatic sulfone, polyvinylidene fluoride, polymethyl methacrylate or its graft copolymer, thermoplastic polyurethane elastomer rubber, polyethylene terephthalate, polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride and polyvinylidene fluoride-hexafluoropropylene.

[0045] As a preferred embodiment of the viscous microspheres, the viscous microspheres are made of PMMA or styrene-grafted PMMA, and the glass transition temperature Tg of the material is 30 to 110°C, such as 30°C, 40°C, 45°C, 50°C, 55°C, 60°C, 70°C, 80°C, 90°C, 100°C and 110°C. In a more preferred embodiment, Tg can be limited to 45 to 75°C, and further to 50 to 55°C. The median particle size D of the viscous microspheres is v50 The diameter of the microspheres is 1 to 10 μm, such as 1 μm, 1.5 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm and 10 μm, preferably 3 to 6 μm; the density of the viscous microspheres is 1.1 to 1.3 g / cm 3 , for example 1g / cm 3 , 1.1g / cm 3 , 1.15g / cm 3 , 1.19g / cm 3 , 1.2g / cm 3 , 1.25g / cm 3 and 1.3 g / cm 3 , and further select 1.11~1.2g / cm 3 .

[0046] As a preferred embodiment of the present invention, the solid matter mass ratio of inorganic particles to sticky microspheres is 11:1 to 30:1, preferably 13:1 to 25:1, such as 11:113:1, 15:1, 20:1, 22:1, 25:1, and 30:1.

[0047] As a preferred embodiment of the present invention, the material of the base film is polyethylene and / or polypropylene, and the thickness of the base film is 5 to 15 μm, such as 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm and 15 μm.

[0048] As a preferred embodiment of the present invention, a ceramic coating is coated on one or both surfaces of the base film, and adhesive microspheres are embedded in each ceramic coating.

[0049] In view of the existing technical problems, the second aspect of the present invention provides a method for preparing the aforementioned coated battery separator, such as Figure 3As shown, at least the following steps are included:

[0050] S1: preparing a slurry, that is, mixing and dispersing inorganic particles with a dispersion medium to form an inorganic dispersion, and then adding a solution of viscous microspheres, dispersing them evenly and sieving them to obtain a mixed slurry. The prepared slurry at least includes a mixed slurry;

[0051] S2: coating, i.e. coating the slurry onto the base film to form a ceramic coating embedded with adhesive microspheres on the base film;

[0052] S3: Drying, i.e. drying the base film after coating the slurry to obtain a coated battery separator with high adhesion and low Hi-Pot defect.

[0053] The solid content of the slurry is 28-40%, such as 28%, 30%, 32%, 34%, 36%, 38% and 40%;

[0054] The material of the sticky microsphere is PMMA or its graft copolymer. The solid content of PMMA or its graft copolymer in the sticky microsphere solution is 15-30%, such as 15%, 17%, 20%, 23%, 26%, 29% and 30%. The solid content of the sticky microsphere directly affects the floating degree of the sticky microsphere. The higher the solid content, the smaller the floating degree, and the easier the sticky microsphere contacts the surface of the base film. By limiting the range of the solid content, the floating and sinking phenomena of the sticky microsphere are avoided. The density of the sticky microsphere raw material is 1.1-1.3 g / cm 3 , for example 1g / cm 3 , 1.1g / cm 3 , 1.15g / cm 3 , 1.19g / cm 3 , 1.2g / cm 3 , 1.25g / cm 3 and 1.3 g / cm 3 , 1.11~1.2g / cm 3 For better.

[0055] If the slurry in step S1 only includes mixed coating slurry, a single-layer coating process is adopted, that is, a single-layer slurry is coated on the surface of the base film (single or double sides) at one time to form a ceramic layer embedded with adhesive microspheres.

[0056] As another embodiment, in order to more easily control the embedding depth of the sticky microspheres so that they do not contact the base film, a double-layer coating process can be adopted, that is, in step S1, the slurry also includes a ceramic slurry without sticky microspheres, the inorganic particles are mixed with the dispersion medium, dispersed evenly and sieved to obtain a ceramic slurry, and in step S2, the ceramic slurry is first coated on the base film, and then the mixed slurry is coated after drying, that is, the ceramic slurry and the mixed slurry are coated on the surface of the base film (single or double sides) in sequence twice to form a ceramic coating with an inner layer without sticky microspheres embedded and an outer layer with sticky microspheres embedded, respectively.

[0057] As a preferred implementation scheme of the method of the present invention, in step S2, a coating machine is used to coat the mixed slurry onto the base film, and the coating speed is 50 to 250 m / min, such as 50 m / min, 100 m / min, 150 m / min, 200 m / min and 250 m / min. A more preferred implementation scheme can further limit the coating speed to 100 to 150 m / min.

[0058] As a preferred embodiment of the mixed coating slurry, the mixed coating slurry further comprises one or more of a thickener, a binder, a wetting agent and a dispersant; further preferably, the mass percentage of each component is:

[0059] Inorganic particles 25-46%, such as 25%, 27%, 30%, 33%, 35%, 38%, 40%, 43% and 46% can be selected;

[0060] Adhesive microspheres 1-30%, such as 1%, 5%, 10%, 15%, 20%, 25% and 30% can be selected;

[0061] Binder 2-10%, such as 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% and 10% can be selected;

[0062] Thickener 0.1-5%, such as 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% and 5%;

[0063] Dispersant 0.01-3%, such as 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.4%, 2.7% and 3% can be selected;

[0064] Wetting agent 0.01-3%, such as 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.4%, 2.7% and 3%;

[0065] The dispersion medium is 50-80%, such as 50%, 52%, 54%, 56%, 58%, 60%, 62%, 64%, 66%, 68%, 70%, 72%, 74%, 76%, 78% and 80% can be selected.

[0066] As a preferred embodiment of the ceramic slurry, the ceramic slurry further comprises one or more of a thickener, a binder, a wetting agent and a dispersant; further preferably, the mass percentage of each component is:

[0067] Inorganic particles 25-46%, such as 25%, 27%, 30%, 33%, 35%, 38%, 40%, 43% and 46% can be selected;

[0068] Binder 1-10%, such as 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% and 10%;

[0069] Thickener 0.1-5%, such as 0.1%, 0.2%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% and 5%;

[0070] Dispersant 0.01-3%, such as 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.4%, 2.7% and 3% can be selected;

[0071] Wetting agent 0.01-3%, such as 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.4%, 2.7% and 3%;

[0072] Dispersing medium 40-60%, such as 40%, 45%, 50%, 55% and 60% can be selected.

[0073] The binder is one or any combination of styrene-butadiene rubber, acrylate, polyvinyl alcohol, polyacrylonitrile, polyvinylidene fluoride, polyethylene oxide and polytetrafluoroethylene.

[0074] The thickener is one or more of sodium carboxymethyl cellulose, carboxymethyl cellulose, lithium carboxymethyl cellulose, sodium alginate, polyacrylamide, polyacrylic acid, polyvinyl alcohol, polyimide and cellulose; preferably, polyether-modified siloxane.

[0075] The wetting agent is one or more of anionic surfactants, polyethylene surfactants and polyol surfactants; polyvinyl pyrrolidone is preferred.

[0076] The dispersant is one or more of polyvinyl pyrrolidone, polyacrylamide and polyvinyl alcohol.

[0077] Pure water is usually used as the dispersion medium.

[0078] As an example of the mixed coating slurry, 27 parts of boehmite (Y-A1OOH, hydrated alumina; manufactured by Anhui Yishitong Company, BG611, D v50 0.8 μm) and 0.2 g polyvinyl pyrrolidone (solid content 50%) were dispersed in 60.2 parts of water, and dispersed by sand mill (speed 1000 rpm, 30 min) to form a dispersion, and 7 parts of sticky microspheres (Tg = 50 ° C, D v50 =3μm, solid content 25%), after being evenly dispersed, 3 parts of acrylate (solid content 45%), 2.4 parts of sodium carboxymethyl cellulose (solid content 4%) and 0.2 parts of polyether modified siloxane (solid content 100%) were added in sequence, dispersed evenly and sieved to form a mixed slurry with boehmite and sticky microspheres as the main materials.

[0079] The above-mentioned viscous microspheres, when the density is 1.2, are polymethyl methacrylate (Shandong Sailins Biotechnology Co., Ltd., PMPMS-1.2); when the density is 1.19, they are polymethyl methacrylate grafted with styrene (Zhejiang Jingtong Technology Co., Ltd., ACRYSPHERE MT).

[0080] As an example of ceramic slurry, 36 parts of boehmite (same as above) and 0.2g polyvinyl pyrrolidone (solid content 50%) are dispersed in 58 parts of water, and dispersed by sand mill (rotation speed is 1000rpm, 30min) to form a dispersion, and 3 parts of acrylate (solid content 45%), 2.7 parts of sodium carboxymethyl cellulose (solid content 4%), and 0.1 part of polyether modified silicone (solid content 100%) are added in sequence, dispersed evenly and sieved to form a ceramic slurry with boehmite as the main material.

[0081] As a preferred embodiment of the method of the present invention, in step S2, the mixed coating slurry is coated on one or both surfaces of the base film to form a base film with a ceramic coating.

[0082] In view of the existing technical problems, the third aspect of the present invention provides a secondary battery, comprising the aforementioned coated battery separator, or comprising a coated battery separator prepared by the aforementioned method for preparing the coated battery separator.

[0083] The following are specific test examples and comparative examples of the present invention. Unless otherwise specified, the raw materials, reagents, methods, etc. used in the examples are conventional raw materials, reagents, methods in the art. The parts referred to below are all measured by mass, with pure water as the mass standard.

[0084] The following test examples 1 to 19 all use boehmite as the main material of the ceramic coating, the sticky microspheres are PMMA or its graft copolymer microspheres, the binder is acrylate with a solid content of 45%, the thickener is sodium carboxymethyl cellulose with a solid content of 4%, the wetting agent is polyether-modified siloxane with a solid content of 100%, the dispersant is polyvinyl pyrrolidone with a solid content of 50%, and the dispersion medium is water. Among them: Test examples 1 to 10 use a double-layer coating process, and test examples 11 to 19 use a single-layer coating process.

[0085] The parameter settings not described in detail in the above test examples are detailed in Table 1 and will not be repeated here.

[0086] For each example, the data obtained through the performance test include embedding depth h, bonding strength, powder loss rate, thermal shrinkage rate (MD130℃ and TD130℃), and the proportion of the sticky microspheres protruding from the outer surface of the ceramic coating. The specific test method is as follows:

[0087] (1) Embedment depth h (μm)

[0088] The embedding depth h is the vertical distance between the bottom of the sticky microsphere and the outer surface where it is embedded. Ten 5 cm × 5 cm coated membrane samples were cut, 5 of which were cut vertically along the TD direction. The vertical distance between the bottom of the sticky microsphere marked as i and the outer surface of the coating within the scope of the microscope was measured using a Zeiss field emission scanning electron microscope (ZEISS SIGMA 300 at 500 times the field of view of the electron microscope) and recorded as the embedding depth h. i1 , the embedding depth of all microspheres in the TD section Test 5 samples and take the average value h TD′ The other 5 samples were cut vertically along the MD direction and measured using a Zeiss field emission scanning electron microscope (ZEISSSIGMA 300, 500 times the field of view of the electron microscope). The vertical distance between the bottom of the sticky microsphere marked as i and the outer surface of the coating was recorded as the embedding depth h. i2 , the embedding depth of all microspheres in the MD section Test 5 samples and take the average value h MD′ ; The calculated embedding depth h is:

[0089]

[0090] (2) Bond strength (N / m)

[0091] Cut samples of 25mm×20mm size, electrodes of 25mm×60mm size and A4 paper of 21mm×50mm size, and stack them in the order of A4 paper, diaphragm, electrode, and A4 paper from top to bottom, with the A4 paper leaking out at a distance of more than 3cm above and below. Use a hot press (Qmesys, QM940AS) for 30s, where the temperature of the upper and lower clamps of the hot press is 85℃ and the pressure is 1000kgf. After the hot pressing, the sample is manually peeled off by 5mm, and the electrode is clamped by the lower chuck of a tensile testing machine (Jinan Sike Testing Technology Co., Ltd., TSL-1002), and the diaphragm is clamped by the upper chuck to ensure that there is no tilt. The tensile speed is 300mm / min, and the measurement is made three times to take the average value.

[0092] (3) Powder loss rate (%)

[0093] Cut the battery separator into 6 pieces, 3cm×22cm in size, and place them on an analytical balance to weigh them. Record the weight as m 1 ; Make sure the curved table of the friction color fastness tester (Daei Kagaku Seiki Manufacturing Co., Ltd., RT-300S) is clean, fix the lens paper on the friction head of the friction color fastness tester, with the smooth side of the lens paper facing outward, then fix the cut battery diaphragm on the curved table of the friction color fastness tester, with one side of the heat-resistant coating facing up, clamp it and gently place the friction head on the diaphragm, set the number of experiments to 5 on the operation panel of the color fastness tester and click to start. After the experiment, take out the battery diaphragm, place it on the analytical balance for weighing, and record the weight as m 2 . Powder loss M = m 1 -m 2 , taking the average value of six groups of diaphragm test data, the powder loss rate is:

[0094]

[0095] If the diaphragm is a double-layer coating on both sides of the base film, the weight of the diaphragm after friction test on both sides is m. 2 , and use this to calculate the powder loss rate data.

[0096] (4) Thermal shrinkage (%):

[0097] The test was conducted in accordance with the requirements of GB / T36363-2018. A sample of 10 cm × 10 cm was cut, and the horizontal TD and vertical MD directions were marked on the sample. The horizontal and vertical widths were measured using a fully automatic image measuring projector (Kunshan Gaopin Precision Instrument Co., Ltd., GP-300C). The sample was clamped between two sealed A4 papers, and placed in a 130°C oven for 1 hour. After the sample returned to room temperature, the horizontal and vertical widths were measured using a fully automatic image measuring projector. The measurements were performed three times, and the average value was taken.

[0098]

[0099] (5) Proportion of sticky microspheres protruding from the outer surface of the ceramic coating (%)

[0100] Ten 5 cm × 5 cm separator samples were cut, of which five were cut vertically along the TD direction. The number of sticky microspheres within the scope of the microscope was recorded as n using a Zeiss field emission scanning electron microscope (ZEISS SIGMA 300 at 500 times the field of view). 1 The number of sticky microspheres protruding from the outer surface of the ceramic coating is n 2 , the percentage of sticky microspheres protruding from the outer surface of the ceramic coating in the TD direction is n TD =n 2 / n 1 , repeat the test for 5 groups of samples and take the average value;

[0101] The other 5 parts were cut vertically along the MD direction and observed using a Zeiss field emission scanning electron microscope (ZEISSSIGMA 300 at 500 times the field of view of the electron microscope). The number of sticky microspheres was recorded as n. 3 The number of sticky microspheres protruding from the outer surface of the ceramic coating is n 4 , the proportion of sticky microspheres protruding from the outer surface of the ceramic coating in the MD direction is n MD =n 4 / n 3 , repeat the test for 5 groups of samples and take the average value. The percentage of microspheres protruding from the outer surface of the ceramic coating is (n TD +n MD ) / 2.

[0102] The performance test of the battery separator of the test example is carried out, and the test results are shown in the following table:

[0103] Table 1: Comparison of physical properties of test examples

[0104]

[0105]

[0106] Table 1-1 continued:

[0107]

[0108]

[0109] Continued Table 1-2:

[0110]

[0111]

[0112] Continued Table 1-3:

[0113]

[0114]

[0115] The above-mentioned sticky microspheres are polymethyl methacrylate (Shandong Selins Biotechnology Co., Ltd., PMPMS-1.2) when the density is 1.2; and polymethyl methacrylate grafted with styrene (Zhejiang Jingtong Technology Co., Ltd., ACRYSPHERE MT) when the density is 1.19.

[0116] It can be seen from Table 1, 1-1, 1-2 and 1-3 above that:

[0117] In the coated battery separator of the present invention, for any one of the above-mentioned sticky microspheres, the vertical distance from the bottom of the sticky microsphere to the outer surface is the embedding depth h, and the coating thickness H satisfies H / 3 < h ≤ H / 2. Further, 60-98% of the sticky microspheres protrude from the outer surface of the ceramic coating. The coated battery separator satisfying the above limitations has a relatively high bonding strength, a relatively small thermal shrinkage rate, and a relatively small powder loss rate; it can be seen from the comparison of Test Examples 1-2 and Test Examples 6-7 that when the polymer microspheres are polymethyl methacrylate grafted with styrene and its density is 1.19 g / cm 3 at this time, it has better bonding strength, better thermal stability, and a smaller powder loss rate; it can be seen from the comparison of Test Examples 1-3 and Test Examples 8-9 that when the mass ratio of inorganic particles to sticky microspheres is 11:1 to 30:1, it can take into account better bonding strength, better thermal stability, and a smaller powder loss rate; it can be seen from the comparison of Test Examples 1-10 and Test Examples 11-19 that, compared with double-layer coating, single-layer coating has a smaller powder loss rate.

[0118] In the description of the present invention, it should be noted that the orientation or positional relationship indicated by the terms "inner", "outer", "vertical", etc. is only for the convenience of describing the present invention, rather than indicating or implying that the device or element referred to must have a specific orientation or be constructed and operated in a specific orientation. Therefore, it should not be construed as a limitation of the present invention. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0119] Although the test examples of the present invention have been shown and described above, it can be understood that the above test examples are exemplary and should not be construed as a limitation of the present invention. Those of ordinary skill in the art can make changes, modifications, substitutions, and variations to the above test examples within the scope of the present invention.

Claims

1. A coated battery separator, comprising a base film and a coating coated on at least one surface of the base film, wherein the coating is a ceramic coating containing inorganic particles, characterized in that: The ceramic coating is embedded with a plurality of sticky microspheres; the contact surface between the ceramic coating and the base film is the inner surface, the other opposite surface is the outer surface, the vertical distance between the bottom of the sticky microsphere and the outer surface is the embedding depth h, the thickness of the ceramic coating is H, and for any of the sticky microspheres, H / 3 is satisfied <h≤H / 2。 2. The coated battery separator according to claim 1, characterized in that 60-98% of the number of the adhesive microspheres protrude from the outer surface of the ceramic coating.

3. The coated battery separator according to claim 1, characterized in that The material of the inorganic particles includes one or more of α-alumina, γ-alumina, boehmite, calcium carbonate, barium sulfate, barium titanate, hydrotalcite, montmorillonite, spinel, titanium dioxide, silicon dioxide, zirconium dioxide, magnesium oxide, calcium oxide, beryllium oxide, magnesium hydroxide, calcium hydroxide and silicon carbide; The median particle size D of the inorganic particles v50 0.05~1.5μm.

4. The coated battery separator according to claim 1, characterized in that The viscous microspheres are polymer microspheres, and their materials include one or more of polyimide, styrene-butadiene rubber, modified polyacrylate, polyetherimide, aramid, aramid fiber, polyvinylidene fluoride, polymethyl methacrylate or its graft copolymer, thermoplastic polyurethane elastomer rubber, polyethylene terephthalate, polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride and polyvinylidene fluoride-hexafluoropropylene.

5. The coated battery separator according to claim 1, characterized in that The viscous microspheres are polymethyl methacrylate microspheres or graft copolymer microspheres thereof, and the glass transition temperature of the viscous microspheres is 30 to 110° C.; the D v50 The diameter of the adhesive microsphere is 1-10 μm, and the density of the adhesive microsphere is 1.1-1.3 g / cm 3 .

6. The coated battery separator according to claim 5, characterized in that The solid matter mass ratio of the inorganic particles to the adhesive microspheres is 11:1 to 30:1, preferably 13:1 to 25:

1.

7. The coated battery separator according to claim 1, characterized in that The base film is made of polyethylene and / or polypropylene, and has a thickness of 5 to 15 μm.

8. The coated battery separator according to any one of claims 1 to 7, characterized in that: The ceramic coating is coated on one or both surfaces of the base film.

9. A method for preparing a coated battery separator according to any one of claims 1 to 8, characterized in that: At least the following steps are included: Preparing the slurry: mixing and dispersing the inorganic particles with the dispersion medium to form an inorganic dispersion, then adding the solution of the viscous microspheres, dispersing them evenly and sieving them to obtain a mixed slurry, wherein the prepared slurry at least includes the mixed slurry; Coating: coating the slurry onto a base film to form a ceramic coating layer embedded with adhesive microspheres on the base film; Drying: drying the base film coated with the slurry to obtain the coated battery separator; The solid content of the mixed slurry is 28-40%; The viscous microspheres are polymethyl methacrylate microspheres or graft copolymer microspheres thereof. The solid content of polymethyl methacrylate or graft copolymer thereof in the viscous microsphere solution is 15-30%. The density of the viscous microsphere raw material is 1.1-1.3 g / cm 3 ; The slurry further comprises one or more of a thickener, a binder, a wetting agent and a dispersant; The mass percentages of the components in the mixed slurry are: 25-46% inorganic particles, 1-30% sticky microspheres, 2-10% binder, 0.1-5% thickener, 0.01-3% dispersant, 0.01-3% wetting agent and 50-80% dispersion medium; In the coating step, a coating machine is used to coat the mixed coating slurry onto the base film at a coating speed of 50 to 250 m / min.

10. The method for preparing a coated battery separator according to claim 9, characterized in that: The following steps are also included: In the slurry preparation step, the slurry further includes a ceramic slurry without adhesive microspheres, and the inorganic particles are mixed with a dispersion medium, dispersed uniformly and sieved to obtain the ceramic slurry; In the coating step, the ceramic slurry is first coated on the base film, and then the mixed coating slurry is coated after drying; The mass percentages of the components in the ceramic slurry are: 25-46% of inorganic particles, 1-10% of binder, 0.1-5% of thickener, 0.01-3% of dispersant, 0.01-3% of wetting agent and 40-60% of dispersion medium.

11. The preparation method according to claim 10, characterized in that: The binder is one or more of styrene-butadiene rubber, acrylate, polyvinyl alcohol, polyacrylonitrile, polyvinylidene fluoride, polyethylene oxide and polytetrafluoroethylene; The thickener is one or more of sodium carboxymethyl cellulose, carboxymethyl cellulose, lithium carboxymethyl cellulose, sodium alginate, polyacrylamide, polyacrylic acid, polyvinyl alcohol, polyimide and cellulose; The wetting agent is one or more of anionic surfactants, polyethylene surfactants and polyol surfactants; The dispersant is one or more of polyvinyl pyrrolidone, polyacrylamide and polyvinyl alcohol.

12. The preparation method according to any one of claims 9 to 10, characterized in that: The mixed coating slurry is coated on one or both surfaces of the base film.

13. A secondary battery, characterized in that: The invention comprises the coated battery separator according to any one of claims 1 to 8, or comprises a coated battery separator prepared by the method for preparing the coated battery separator according to any one of claims 9 to 12.